2020
DOI: 10.3390/md18060312
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a New β-Galactosidase from Alteromonas sp. QD01 and Its Potential in Synthesis of Galacto-Oligosaccharides

Abstract: As prebiotics, galacto-oligosaccharides (GOSs) can improve the intestinal flora and have important applications in medicine. β-galactosidases could promote the synthesis of GOSs in lactose and catalyze the hydrolysis of lactose. In this study, a new β-galactosidase gene (gal2A), which belongs to the glycoside hydrolase family 2, was cloned from marine bacterium Alteromonas sp. QD01 and expressed in Escherichia coli. The molecular weight of Gal2A was 117.07 kDa. The optimal pH and temperature of Gal2A were 8.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Optimisation regarding temperature were observed by previously (Hsu et al, 2005, Gobinath et al, 2014, Li et al, 2020 where β-gal synthesis was stable at 40 to 45°C, however, 35°C was found to be optimum for L. fermentum and above 50°C there was a rapid decrease in enzyme synthesis as well for the growth of the organism due to thermostability of enzyme (Cho et al, 2003;Rao and Dutta, 1977). β-gal production was prominent in the range 5.5 to 7.0 (p<0.05) as reported by others (Gobinath and Prapulla, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…Optimisation regarding temperature were observed by previously (Hsu et al, 2005, Gobinath et al, 2014, Li et al, 2020 where β-gal synthesis was stable at 40 to 45°C, however, 35°C was found to be optimum for L. fermentum and above 50°C there was a rapid decrease in enzyme synthesis as well for the growth of the organism due to thermostability of enzyme (Cho et al, 2003;Rao and Dutta, 1977). β-gal production was prominent in the range 5.5 to 7.0 (p<0.05) as reported by others (Gobinath and Prapulla, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, we expressed it in the baculovirus expression system, and high enzyme activity was detected. The optimal pH and temperature for β‐galactosidase of many bacteria and fungi were found in the range of 6.5–4.5 and 40–60 °C, respectively (Carneiro, Yu, Dupree, & Ward, 2018; Li et al, 2020; Xia et al, 2018; Yang et al, 2018). However, the optimum pH and temperature of some β‐galactosidase are not in this range, for example, β‐galactosidase from Aspergillus lacticoffeatus (Cardoso, Silverio, Abrunhosa, Teixeira, & Rodrigues, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most metal ions promoted the activity of β‐galactosidase from Alteromonas sp . QD01, especially Mn 2+ and Mg 2+ (Li et al, 2020). According to the analysis of influences caused by metal ions to BmGal, we found that iron ions can stimulate the activity of the enzyme while cobalt, nickel, or lead ions can inhibit its activity significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Galactosidase (EC 3.2.1.23), also referred to as lactase, is an important member of glycosyl hydrolase, which can hydrolyze O -glycosidic bonds of lactose by hydrolysis reaction, resulting in the production of glucose and galactose ( Vera et al, 2017 ; Singh et al, 2019 ). Treating dairy products with β-galactosidase through pre-hydrolyzation that can reduce lactose concentration offers a promising solution ( Li et al, 2020 ). Thus far, numerous β-galactosidases were purified, cloned, and characterized from bacteria ( Mavromatis et al, 2010 ; Tian et al, 2013 ), fungi ( Rico-Díaz et al, 2017 ), yeast ( de Freitas et al, 2020 ), plants ( Deng et al, 2019 ), and mammals ( He et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%